Simulation Studies of Fault Events in 66 kV Superconducting Cable - Masuda, Takato; Morimura, Toshiya; Minamino, Tadahiko; Saito, Takahiro; Ashibe, Yuichi; Yamaguchi, Hirohito; Mimura, Tomoo (IEEE Transactions on Applied Superconductivity, 2021)
Superconducting cables have been developed around the world and demonstrated its operation in the grid. One of the important subjects is to study what happens in case of fault events, such as a ground fault, short circuit fault and so on, occurred in the superconducting cable. Therefore, we have conducted experimental and numerical simulations at the fault events. For the short circuit accidents, we conducted experimental simulation with a 66 kV 3-core cable in 40 m length to measure LN 2 temperatures and pressures in the cable during and after simulated fault current as 16 kA- 8 sec, which has the same heat generation as the worst fault condition in the Japanese 66 kV network as 31.5 kA for 2 sec. The measured values of temperature and pressure are almost good agreement with calculated values. Using the same calculation code, temperatures and pressures at the fault event are estimated in the superconducting cable with 3 km length for practical use. As the results, in case of 31.5 kA in 2 sec, maximum temperature at superconducting conductor is calculated as 112 K and maximum pressure is as 3 MPa under the base pressure of 1 MPa. In that case, no gasification of LN 2 is occurred. So, blowout of cryostat would not be occurred. However, it expects that several hours are necessary to turn back original state. For the ground fault, we conducted experimental simulations using samples with protection sheets and short cable samples. The fault current condition is assumed as 1.5 kA for 2 sec, which is the worst case in the Japanese 66 kV network. In such condition, the cable cryostat can be penetrated by the arc energy of the insulation break down and then LN 2 would be blown out to make some damage for surrounding apparatus. So, we conducted LN 2 leakage test in the manhole to measure LN 2 accommodation level and concrete temperatures. Using experimental results and diffusion equation with thermal conductivity of concrete, inner pressure of manhole was simulated. The calculation results show the pressure rising is not so fast that the manhole lid can be blown off.